Pemberdayaan Masyarakat Melalui Pelatihan Pembuatan Keripik Daun Singkong Sebagai Alternatif Usaha Masyarakat Desa Pucak Kecamatan Tompobulu Kabupaten Maros - Abdul Rahman Mus; Ramlawati; Muh. Arif (Pusat Riset dan Inovasi Nasional, 2023)
This community service activity program is in collaboration with villages supported by the Indonesian Muslim University. This activity aims to increase and grow the knowledge of the Pucak village community regarding the development of economical products from cassava leaves, namely processing them into cassava leaf chips. This activity will be carried out in Pucak village, Tompubolo District, Maros Regency. Based on the situation analysis in Pucak Village, Tompubolo District, Maros Regency, several problems arise, namely: 1) The low level of public knowledge about cassava leaves which can be processed into new products on a household scale. 2) It is necessary to arouse public interest in increasing consumption value to increase income from a commodity, including cassava leaves. Based on the results of initial observations and interviews conducted with the village, it can be concluded that the problems and conditions of partners in Pucak village are that it is known that the source of income for the people of Pucak village is daily income whose nominal value is uncertain. Therefore, the solution offered to Pucak Village, Tompobulu District, Maros Regency is that the community service implementation team will carry out outreach and practice in making economical products of cassava leaf chips which have sales value and can increase household economic income.